Eyeball Movement Detection To Control Smart Wheelchair Using Eye Aspect Ratio (EAR) - Pangestu, Gusti (MATICS, 2021)
Many developed technology's with an aim of helping the disabilities. One of them is a wheelchair. It is the most common stuff that used for helping disabilities as a tool for mobilization. There are two types of wheelchair. The first is the manual wheelchair, operated by hand. The second is an electrical wheelchair, that operated by joystick or other electric device. This research proposed a mechanism to control the wheelchair by using an eye movement. It could be used especially for people with multiple disabilities (hand and foot defects), so they can take an advantage of their eyeballs as a tool to control wheelchair movement. There are five options for controlling the wheelchair (leftward, rightward, upward, downward and center). Leftward, rightward and center used for control direction of smart wheelchair. Furthermore, upward and downward of eye movements used to control the speed of smart wheelchair. Upward command used to increase the speed. Meanwhile, down-ward used to decrease the speed (stop). The proposed method used EAR (Eye Aspect Ratio), which divided into three regions based on sector area, for determining the directions of the eyeball movement. EAR is the value that represents the ratio between the upper eyelid and lower eyelid. The result obtained high accuracy